The Effects of Sodium Hydroxide (NaOH) Concentration and Reaction Temperature on The Properties of Biodiesel from Philippine Tung (Reutealis Trisperma) Seeds - Slamet Supriyadi; Purwanto Purwanto; Didi Dwi Anggoro; Hermawan Hermawan (Automotive Experiences, 2022)
Philippine Tung (Reutealis trisperma) is an indigenous nut that is a relatively new feedstock for producing biodiesel in Indonesia. The nature of NaOH base catalyst and reaction temperature plays an important role in the method of biodiesel production. This study aimed to assess the effects of different percentages of NaOH base catalyst and reaction temperature on physicochemical properties of Philippine Tung biodiesel. Transesterification process was carried out by reacting Philippine Tung oil with methanol and NaOH catalyst. NaOH weight to oil weight was at 0.25%, 0.5%,0.75% and 1%, the reaction temperature set up were at 60Â°C and 70Â°C, while methanol-oil molar ratio was set at 6:1. Yield, acid value, saponification value, density, and viscosity of biodiesel were significantly influenced by NaOH catalyst concentrations. Meanwhile reaction temperature had no effect on the yield and viscosity. Philippine Tung biodiesel produced using 0.25% NaOH catalyst met the SNI 04-7182-2015 biodiesel standard of the properties investigated in this study (yield: 96.18%, acid value: 0.466 mg KOH/g, saponification value: 200.083 mg KOH/g, density: 0.889 g/mL, viscosity: 5.276 cSt).